Intranasal vaccination with a Newcastle disease virus-vectored vaccine protects hamsters from SARS-CoV-2 infection and disease - Bryce M. Warner (Elsevier, 2021)
Summary: The pandemic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of coronavirus disease 2019 (COVID-19). Worldwide efforts are being made to develop vaccines to mitigate this pandemic. We engineered two recombinant Newcastle disease virus (NDV) vectors expressing either the full-length SARS-CoV-2 spike protein (NDV-FLS) or a version with a 19 amino acid deletion at the carboxy terminus (NDV-Δ19S). Hamsters receiving two doses (prime-boost) of NDV-FLS developed a robust SARS-CoV-2-neutralizing antibody response, with elimination of infectious virus in the lungs and minimal lung pathology at five days post-challenge. Single-dose vaccination with NDV-FLS significantly reduced SARS-CoV-2 replication in the lungs but only mildly decreased lung inflammation. NDV-Δ19S-treated hamsters had a moderate decrease in SARS-CoV-2 titers in lungs and presented with severe microscopic lesions, suggesting that truncation of the spike protein was a less effective strategy. In summary, NDV-vectored vaccines represent a viable option for protection against COVID-19.